Od idoli religijnych do idolatrycznej filozofii. Rozważania polemiczne wokół książki Ireneusza Ziemińskiego Religia jako idolatria - Sobota, Daniel Roland 1978- (2021)
The article presents the main theses of the latest book by Ireneusz Ziemiński, entitled Religia jako idolatria. Esej filozoficzny o nieuchronności elementów idolatrycznych w religii [Religion as Idolatry. A Philosophical Essay on the Inevitability of Idolatry Elements in Religion] (Szczecin 2020) and criticizes its weaknesses. It draws attention to the shortcomings of methodological awareness, the dogmatic definition of idolatry, the unauthorized extension of the concept of idolatry to all religious and even cultural phenomena, a false understanding of man, symbol, ritual, religious experience and its expression, and finally falling into a performative contradiction.
Keywords: Idol; Idolatry